Quasi-Static and High Strain Rate Properties of a Cross-Ply Metal Matrix Composite - Hall, Ian W.; Taşdemirci, Alper; Taşdemirci, Alper; Derrick, J. (Elsevier Ltd., 2009)
A series of compression tests has been carried out at quasi-static and high strain rates on cylindrical samples of an alumina fiber/Al-6061 metal matrix composite. The composite plates were prepared with fibers in the 0°, 0/90° and ±45° orientations. It was found that the mechanical properties were strongly dependent upon the imposed strain rate, with fracture stress increases of >50% being noted for several orientations at high strain rates: these increases are not believed to be related to strain rate sensitivity of either the matrix or fibers but to arise from the inertia of fragments which remain in place after fracture and continue to bear load. Also, and in contradiction to behavior anticipated from the rule of mixtures, it was found that 0/90° samples exhibited properties superior to those of 0° unidirectional samples. High-speed photography was used to confirm the sequence of deformation and fracture events at high strain rate. © 2008 Elsevier B.V. All rights reserved.
Keywords: Strain rate; Compression; High strain rate; Metal matrix composites; Cross-ply